1974
DOI: 10.1111/j.1348-0421.1974.tb00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Morphology of Vibrio parahaemolyticus (Fujino et al) Sakazaki, Iwanami and Fukumi 19631

Abstract: The flagellar morphology of 88

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…However, some species of vibrios possess unsheathed lateral (L-) flagella in addition to M-flagella when the bacteria are grown on agar media (1,2). The two kinds of flagella are distinguished from each other morphologically (2,20), functionally (13) and immunologically (11). We demonstrated that two different antigenic determinant groups, namely, a surface antigenic determinant (SA) and an internal antigenic determinant (IA), exist on both flagella (14)(15)(16).…”
mentioning
confidence: 96%
“…However, some species of vibrios possess unsheathed lateral (L-) flagella in addition to M-flagella when the bacteria are grown on agar media (1,2). The two kinds of flagella are distinguished from each other morphologically (2,20), functionally (13) and immunologically (11). We demonstrated that two different antigenic determinant groups, namely, a surface antigenic determinant (SA) and an internal antigenic determinant (IA), exist on both flagella (14)(15)(16).…”
mentioning
confidence: 96%
“…Lateral flagella were produced only on agar plates (3, 17, 18) and were easily removed from the cells mechanically (17, 18), whereas the single polar flagellum was produced either in liquid medium or on agar plates (3, 17, 18) and could only be removed from the cells by vigorous agitation (7). The single polar flagellum has a sheath-like structure, whereas the lateral flagella do not (1,7,17,18). Moreover, lateral flagella are of the curly type, whereas the single polar flagellum is a normal type (17,181.…”
mentioning
confidence: 99%
“…In addition to the antigenic difference, several other different properties of these two flagella were reported. Lateral flagella were produced only on agar plates (3, 17, 18) and were easily removed from the cells mechanically (17,18), whereas the single polar flagellum was produced either in liquid medium or on agar plates (3, 17, 18) and could only be removed from the cells by vigorous agitation (7). The single polar flagellum has a sheath-like structure, whereas the lateral flagella do not (1,7,17,18).…”
mentioning
confidence: 99%
“…Cross reactivity be tween H-serovars of these two species and other vibrios having lateral flagella, such as V. parahaemolyticus, V. campbellii, V. proteus, or V. fluvialis, was not observed in the H-agglutination test, although partial common antigenicity was observed in the gel diffusion test with flagellin monomers. These observations suggest that surface antigenic determinants of the lateral flagella of V. alginolyticus and V. harveyi are specific to these two species but internal antigenic determinants buried in the flagellar filaments are partially shared with other vibrio species.Some species of genus Vibrio have two kinds of flagella, lateral flagella (Lflagella) and polar monotrichous flagella (M-flagella) (1,4,20). Cells grown in liquid media possess only one M-flagellum on one end of each rod cell, whereas cells grown on agar media have both kinds of flagella on one cell.…”
mentioning
confidence: 99%
“…Some species of genus Vibrio have two kinds of flagella, lateral flagella (Lflagella) and polar monotrichous flagella (M-flagella) (1,4,20). Cells grown in liquid media possess only one M-flagellum on one end of each rod cell, whereas cells grown on agar media have both kinds of flagella on one cell.…”
mentioning
confidence: 99%